Sudan - Strengthening Good Governance for Development Outcomes in Southern Sudan : Issues and Options - World Bank (World Bank, 2012)
This report is the product of a joint Government of Southern Sudan (GoSS) and World Bank initiative aimed at facilitating informed policy making in key areas of public service management. The objective was to facilitate a process in which a Bank-supported team will provide technical inputs and will support appropriate consultation leading to informed and pragmatic policy making and implementation. Coordination, in particular on policy formulation, is difficult and a key constraint in young governments and more so in post-conflict situations such as that of Southern Sudan. Available analytical and executive capacity is already stretched. The number of issues that need to be addressed is large and prioritization is difficult. There are sharp political divisions that are not easily reconciled. The report is presented in two parts. Part one provides the background as well as a summary of findings and recommendations. Chapter one provides a brief historical background and lessons from this experience but may be skipped without loss of continuity. Chapter two presents an overview of the issues and options facing the GoSS in managing the public service, implementing the decentralization vision and tackling corruption and summarizes the findings presented in detail in the second part of the report. Part two covers the three thematic areas that are the subject of this initiative in greater detail: chapter three on public service reform, chapter four on decentralization, and chapter five on corruption. Two annexes document key aspects of the process. A third annex summarizes a paper on traditional authorities prepared as part of this exercise.